2000
DOI: 10.1111/j.1349-7006.2000.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reproduction on Spontaneous Development of Endometrial Adenocarcinomas and Mammary Tumors in Donryu Rats

Abstract: Effects of reproduction on spontaneous development of uterine endometrial adenocarcinomas and mammary tumors in Donryu rats were investigated. While the incidence of endometrial adenocarcinomas in Donryu rats was not influenced by a single reproductive experience (SRE), it showed a tendency to decrease in animals having three reproductive experiences (TRE), compared to the nulliparous case (NRE). In addition, both SRE and TRE animals showed delayed occurrence and decreased incidences and mean numbers of mammar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…[23][24][25] The incidence of spontaneous uterine adenocarcinomas in this rat strain showed a tendency to decrease in animals having reproductive experience, compared to the nulliparous case, suppression being associated with changes in the hormonal milieu. 26) These results indicate that the Donryu rat may be a good animal model for uterine adenocarcinoma linked to endogenous estrogens in humans. An elevated incidence of such tumors develops in this rat strain with a single intra-uterine administration of N-ethyl-N′-nitro-N-nitrosoguanidine (ENNG) and a two-stage rat uterine carcinogenesis model has already been established.…”
mentioning
confidence: 91%
“…[23][24][25] The incidence of spontaneous uterine adenocarcinomas in this rat strain showed a tendency to decrease in animals having reproductive experience, compared to the nulliparous case, suppression being associated with changes in the hormonal milieu. 26) These results indicate that the Donryu rat may be a good animal model for uterine adenocarcinoma linked to endogenous estrogens in humans. An elevated incidence of such tumors develops in this rat strain with a single intra-uterine administration of N-ethyl-N′-nitro-N-nitrosoguanidine (ENNG) and a two-stage rat uterine carcinogenesis model has already been established.…”
mentioning
confidence: 91%
“…A total of 141 Donryu and 145 F344 aging females used as control group animals for long-term carcinogenicity studies 4,7 was selected for histopathological examination. The former animals were examined at 13-28 months of age, and the latter at 13-26 months.…”
Section: ) Aged Ratsmentioning
confidence: 99%
“…Using this strain, we recently demonstrated effects of reproduction on uterine carcinogenesis, in line with the known lower risk of uterine adenocarcinoma in multiparous as compared to nulliparous or infertile women. The incidence of spontaneous endometrial adenocarcinomas showed a tendency to decrease in animals having three reproductive experiences, compared to the nulliparous case, although the incidence was not influenced by a single pregnancy 4 . Thus, this rat strain is a good animal model for endometrial adenocarcinoma development due to the imbalance of endogenous steroid hormones, as found in humans.…”
Section: Introductionmentioning
confidence: 78%